Overview of immigration detention depot (Illegal Immigrant) Immigration Department Sarawak/ Shahrul Azley Senyem - Senyem, hahrul Azley (2014)
In the early years before World War II, the Immigration Department conducted surveillance and inspection work involving the inspection of travellers and travel documents at entry points. Immigration matters were administered by a Senior Officer of the Malayan Civil Service who bore the title of ‘Immigration Officer of the Straits Settlement and Federated Malay States’. He was assisted by the Deputy Immigration Officer, who was actually a police officer, temporarily seconded to the post. They were based in Penang which was the main entry point into Malaya. Other entry points were Changloon, Padang Besar, Kroh and Port Swettenham. The administrative centre was based in Singapore.